2021
DOI: 10.3390/buildings11020048
|View full text |Cite
|
Sign up to set email alerts
|

Macro-Impacts of Air Quality on Property Values in China—A Meta-Regression Analysis of the Literature

Abstract: Air pollution has received increasing attention in recent years, particularly in China, due to the rapid industrialisation that has wrought intense levels of air pollution. A number of studies, therefore, have been devoted to quantifying the impacts of air pollution on property value in China. However, the empirical results are somewhat mixed. This naturally raises questions of whether there is a significant relationship between air quality and housing prices and the plausible reasons for the mixed results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Although the establishment of foreign environmental NGOs together with civil society participation and MNCs growing accountability, our findings fall short in evidencing broader activism in Zhejiang environmental movement, or in China at a large, and this trend is evident in two major protests in Zhejiang, the 2012 “anti-PX” protest in Ningbo (mentioned by two interviewees), or the May 2014 Yuhang protest, where thousands of people gathered in a protest against a planned waste incinerator in a suburb 10 km north-east of Hangzhou (BBC, 2014). These two protests show that mobilization among Chinese civil society happens mostly when community interest is at stake and economic factors like falling property price are threatened (J. Wang et al, 2021), therefore lacking a sense of collective participation toward a sustainable environment.…”
Section: Discussion Toward Growing Political Accountability?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the establishment of foreign environmental NGOs together with civil society participation and MNCs growing accountability, our findings fall short in evidencing broader activism in Zhejiang environmental movement, or in China at a large, and this trend is evident in two major protests in Zhejiang, the 2012 “anti-PX” protest in Ningbo (mentioned by two interviewees), or the May 2014 Yuhang protest, where thousands of people gathered in a protest against a planned waste incinerator in a suburb 10 km north-east of Hangzhou (BBC, 2014). These two protests show that mobilization among Chinese civil society happens mostly when community interest is at stake and economic factors like falling property price are threatened (J. Wang et al, 2021), therefore lacking a sense of collective participation toward a sustainable environment.…”
Section: Discussion Toward Growing Political Accountability?mentioning
confidence: 99%
“…These two protests show that mobilization among Chinese civil society happens mostly when community interest is at stake and economic factors like falling property price are threatened (J. Wang et al, 2021), therefore lacking a sense of collective participation toward a sustainable environment. In both the Ningbo and the Yuhang protests, the local government stopped the plan while relocating it to rural areas where mobilization is less likely due to a lack of an informed middle class (Chen, 2017).…”
Section: Discussion Toward Growing Political Accountability?mentioning
confidence: 99%
“…This also highlights the importance of a dedicated study on office buildings), we will only examine office rent and vacancy rate determinants in this paper. Despite extensive studies of the office sector (An et al [29]; Lee et al [30]; Crosby et al [23]; Khan et al [31]) and housing markets [32,33] internationally, empirical research on Chinese office buildings has been relatively lacking, in part due to its short history as China only adopted its "open door" policy in the late 1970s (Hui et al [34]; Zhang et al [35]). Early research examined Shanghai office rent equilibrium and the related submarkets (Ke & White [36]; White & Ke [37]), and a comparison study was conducted for the Beijing and Shanghai office markets (Ke & White [38]).…”
Section: Literature Review 21 Office Market Researchmentioning
confidence: 99%
“…Long-term exposure to high humidity can not only increase the risk of respiratory diseases such as asthma and rhinitis [19,20], but also create a psychological burden [21]. Fourth, due to the adverse effects of air pollution on public health, residents had a preference for living in housing with better air quality [22,23]. Last, some research has shown that cleanliness is the most important individual variable influencing occupant satisfaction with the overall environment [24].…”
Section: Introduction 1backgroundmentioning
confidence: 99%